2013
DOI: 10.1007/s00520-013-2091-1
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual support of cancer patients and the role of the doctor

Abstract: Spirituality is a universal phenomenon. Patients in a secular society want their doctor to take an interest in their spiritual support and facilitate access to it during illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 40 publications
2
52
0
1
Order By: Relevance
“…(8,9,30,32) This allowed the doctor to provide improved care. (52,58,64) Thus patients distinguished between a doctor asking about spirituality with a view to being aware of this dimension of the patient, versus collecting information in order to deal with spiritual problems within the consultation. In fact, many patients expressed strong objections to doctors acting as spiritual advisors or proselytizing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(8,9,30,32) This allowed the doctor to provide improved care. (52,58,64) Thus patients distinguished between a doctor asking about spirituality with a view to being aware of this dimension of the patient, versus collecting information in order to deal with spiritual problems within the consultation. In fact, many patients expressed strong objections to doctors acting as spiritual advisors or proselytizing.…”
Section: Discussionmentioning
confidence: 99%
“…(63) Barriers to patients talking about R/S with their doctors included thinking it is not part of the physician's job, that doctors did not have the time or were not interested, or that they did not know what to say either because they had not decided or were not ready. (26,32,52,55,66) Hospital patients in one study felt that the vulnerability they experienced by being in their pyjamas discouraged spiritual discussions in a way which would not have been present A c c e p t e d M a n u s c r i p t 18 doctor they knew, rather than a stranger (as found in Theme 1), although it was also suggested that some of these so-called barriers may be excuses for patients who were unwilling to initiate discussion themselves, putting the blame on the doctor. (55) Theme 2 would suggest that it may not be so much a matter of being unwilling so much as disempowered.…”
Section: Do Doctors Ask Their Patients About R/s and If So How Do Thmentioning
confidence: 98%
“…Many models exist for each stage. It is recommended that the purpose of the questioning be considered carefully before a tool is chosen [64,65].…”
Section: Demonstrate the Reflective Capacity To Consider The Importanmentioning
confidence: 99%
“…Beliefs and values are recognised as fundamental elements of current understandings of a person's spirituality and therefore important to any assessment of spiritual needs (Puchalski et al 2014). While current data reveals Australia to be an increasingly secular society (Australian Bureau of Statistics 2016), research demonstrates that patients want their spiritual needs considered as part of their overall health care (Best et al 2014). The provision of spiritual care in response to spiritual needs has increasingly appeared in state and government reports in Australia, and while spiritual care is being provided in Australian hospitals, there has been little attention given nationally to how it is provided, who is providing it and how the contribution of this essential element of care is measured.…”
Section: Introductionmentioning
confidence: 99%